Perawatan apeksifikasi pada gigi permanen muda insisivus pertama kiri atas yang non-vital Apexification treatment of non-vital young permanent left central insicivus - Jenny Krisnawaty; Moch. Richata Fadil; Endang Sukartini; Milly Armilia (DiscoverSys Inc., 2012)
Imperfect young permanent teeth caused by caries or trauma could become necrotic before it’s growth anddevelopment completed, thus causes imperfect shape of the root canal and an opened apex. Difficulty in treatment ofroot canal caused by the absence of apical stop, that makes obturation cannot be accomplished because fillingmaterials will be pushed to periapex. The purpose of this case report was to report the treatment of anterior teethwhich diagnosed as necrotic with apexification. The material filling is calcium hydroxide with strong base natureand give antimicrobacterial effect and tissue liquefaction. The result of the treatment was closure of the apex, thetissue surrounding tooth is in normal range or that absence of radiolusency which is a sign of healing at theperiapical.The conclusion is young permanent tooth which experienced pulp necrotic can be treated withapexification treatment